Turning stories into learning journeys: the principles and methods of Immersive Education - Brunetti, Riccardo; Ferrante, Silvia; Avella, Anna Maria; Indraccolo, Allegra; Del Gatto, Claudia (Frontiers in Psychology, 2024)
This paper describes the theoretical and practical aspects of Immersive Education, an educational methodology based on interactive narratives, articulated as emotional journeys, to develop competencies. It has been developed throughout three school years (2021–2024) with more than 400 students (8–12 years old) in Public Schools in Italy and Spain. Immersive Education can be integrated with curricular school activities and can be used to target both curricular and transversal learning objectives, specifically the ones connected with the Personal, Social and Learning to learn Key Competence (LifeComp European framework). The paper describes the inspirations that led to the creation of the methodology, including similar experiential learning approaches. It then analyses the theoretical principles of the methodology, dividing them in four key-concepts, along with psychological evidence supporting them. The four key-concepts describe how immersive education aims at being a motivation trigger, featuring a dramatic structure, how it is based on the involvement of the self, and how it focuses on fostering a continuous engagement. It continues with a detailed analysis of implementation strategies, specifically about the management of emotional triggers and reactions, enriched by numerous examples taken from the projects implemented with the students. The conclusions open the way to future research directions to measure the impact of this approach on the development of transversal and specific competences.